2020
DOI: 10.3390/ijerph17165987
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Multi-Pronged Intervention on Students’ Perceptions of School Lunch Quality and Convenience and Self-Reported Fruit and Vegetable Consumption

Abstract: School lunch programs provide an opportunity to improve students’ diets. We sought to determine the impact of a multifaceted intervention (cafeteria redesigns, increased points-of-sale and teacher education) on secondary students’ perceptions of school-lunch quality and convenience and fruit and vegetable intake. Surveys (n = 12,827) from middle and high school students in 12 intervention and 11 control schools were analyzed. We investigated change in school-lunch perceptions and lunchtime and daily fruit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Reinforcement and incentives using prompts (Chinchanachokchai et al., 2022; Dave et al., 2015; Erjavec et al., 2021; Machado, Ritchie et al., 2020; Quinn et al., 2018; Song et al., 2016a; Hubbard et al., 2015; Hanks et al., 2013; Hendy et al., 2007; Hoffman et al., 2010; Perry et al., 2004; Taylor, Darby et al., 2013), using rewards (Hendy et al., 2007; Horne et al., 2009; McCormick et al., 2009; Perry et al., 2004; Presti et al., 2015; Taylor, Upton et al., 2013; Wardle et al., 2003, Taylor, Darby et al., 2013), using incentives (Hoffman et al., 2011; Hudgens et al., 2017; Joyner et al., 2017; Machado, Ritchie et al., 2020; McCormick et al., 2009; Wengreen et al., 2021, Ansu et al., 2021, Marcano‐Olivier et al., 2021), using marketing techniques such as characters, banners, and messages, using modeling (role and peer modeling) (Hoffman et al., 2010; Horne et al., 2009; Perry et al., 2004; Taylor, Upton et al., 2013; Hubbard et al., 2015; Birnbaum et al., 2002; Machado, Ritchie et al., 2020; Marcano‐Olivier et al., 2019, 2021; Presti et al., 2015); …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reinforcement and incentives using prompts (Chinchanachokchai et al., 2022; Dave et al., 2015; Erjavec et al., 2021; Machado, Ritchie et al., 2020; Quinn et al., 2018; Song et al., 2016a; Hubbard et al., 2015; Hanks et al., 2013; Hendy et al., 2007; Hoffman et al., 2010; Perry et al., 2004; Taylor, Darby et al., 2013), using rewards (Hendy et al., 2007; Horne et al., 2009; McCormick et al., 2009; Perry et al., 2004; Presti et al., 2015; Taylor, Upton et al., 2013; Wardle et al., 2003, Taylor, Darby et al., 2013), using incentives (Hoffman et al., 2011; Hudgens et al., 2017; Joyner et al., 2017; Machado, Ritchie et al., 2020; McCormick et al., 2009; Wengreen et al., 2021, Ansu et al., 2021, Marcano‐Olivier et al., 2021), using marketing techniques such as characters, banners, and messages, using modeling (role and peer modeling) (Hoffman et al., 2010; Horne et al., 2009; Perry et al., 2004; Taylor, Upton et al., 2013; Hubbard et al., 2015; Birnbaum et al., 2002; Machado, Ritchie et al., 2020; Marcano‐Olivier et al., 2019, 2021; Presti et al., 2015); …”
Section: Resultsmentioning
confidence: 99%
“…Thirteen out of the 16 studies identified reported that incentives such as small prizes (Birnbaum et al., 2002; de Marchi et al., 2020; Hendy et al., 2007; Machado, Ritchie et al., 2020, Marcano‐Olivier et al., 2021), raffle tickets (Machado, Ritchie et al., 2020), virtual currencies (Joyner et al., 2017), and stationery (Horne et al., 2009) increased children's liking, acceptance, willingness to try, and intake of vegetables. Incentives were commonly used together with modeling and education, with most of the interventions reporting positive effects (Birnbaum et al., 2002; Horne et al., 2009; Machado, Ritchie et al., 2020; McCormick et al., 2009; Presti et al., 2015; Song et al., 2016a; Wengreen et al., 2021, Marcano‐Olivier et al., 2021), except from one intervention targeting children with autism, in which no significant effect was reported (Taylor, Upton et al., 2013); however, results from the latter could be attributed to the small sample size ( n = 12) or the special needs of the children. Finally, in a study that used incentives in combination with repeated exposure to sweet peppers, an increase in the peppers’ consumption was only recorded in the exposure group and not in the group that was offered stickers if they would choose a piece of pepper (Wardle et al., 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One question [ 21 ] asked: “adults at school encourage me to eat school lunch” with response options on a 5-point scale from strongly disagree (1) to strongly agree (5).…”
Section: Methodsmentioning
confidence: 99%